2022
DOI: 10.1101/2022.03.30.486421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macroevolutionary diversity of traits and genomes in the model yeast genus Saccharomyces

Abstract: Species is the fundamental unit to quantify biodiversity. In recent years, the model yeast Saccharomyces cerevisiae has seen an increased number of studies related to its geographical distribution, population structure, and phenotypic diversity. However, seven additional species from the same genus have been less thoroughly studied, which has limited our understanding of the macroevolutionary leading to the diversification of this genus over the last 20 million years. Here, we report the geographies, hosts, su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 102 publications
(182 reference statements)
2
13
0
Order By: Relevance
“…Our HTS identified so far uncharacterized S. mikatae Mtt + wild strains as well as the recently reported Mtt + S. mikatae LSYS65-1 strain (Peris et al, 2022). Parallel studies conducted by other authors demonstrated that the two S. jurei strains TUM 629 and D5095 T are also able to utilize wort maltotriose to a certain extent (Giannakou et al, 2021;Hutzler et al, 2021) and that some S. mikatae strains are able to grow on this sugar (Peris et al, 2022).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our HTS identified so far uncharacterized S. mikatae Mtt + wild strains as well as the recently reported Mtt + S. mikatae LSYS65-1 strain (Peris et al, 2022). Parallel studies conducted by other authors demonstrated that the two S. jurei strains TUM 629 and D5095 T are also able to utilize wort maltotriose to a certain extent (Giannakou et al, 2021;Hutzler et al, 2021) and that some S. mikatae strains are able to grow on this sugar (Peris et al, 2022).…”
Section: Discussionsupporting
confidence: 81%
“…Our finding that S. mikatae strains exhibit growth on maltotriose as the sole carbon source provides an example of the high intraspecies phenotypic diversity uncovered recently for the species despite its low genetic diversity (Peris et al, 2022). However, only a limited number of strains have been tested so far for wort fermentability.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, there is clade-specific variation within S. cerevisiae as to whether the MAL1 locus is occupied by the generalist AGT1 or a gene encoding a high-specificity maltose transporter [153], suggesting that domestication may have shaped the genetic architecture of α-glucoside metabolism in this model eukaryote [154]. Supporting this notion, AGT1 homologs can be readily detected in publicly available Saccharomyces genomes, while growth on maltotriose—a sugar transported by AGT1 but not most other maltose transporters—is extremely rare [62]. A notable exception is Saccharomyces jurei, the first wild Saccharomyces reported to grow on maltotriose, which contains a clear homolog of AGT1 that requires extensive starvation or depletion of fermentable carbon sources for its induction [155].…”
Section: Discussionmentioning
confidence: 99%
“…A focal ecological and industrial trait in this wild species is the ability to consume and metabolize the α-glucoside maltose, which is the most abundant sugar in the wort used to brew beer [60,61]. This trait is nearly ubiquitous among isolates of Saccharomyces eubayanus and its sister species Saccharomyces uvarum [62], but it has been lost [63] or severely curtailed [64] in the Holarctic subpopulation of S. eubayanus [51]. Paradoxically, members of this group contain functional structural maltose metabolism genes, and their inability to use this sugar as a carbon source may be due to cis- or trans-regulatory evolution resulting in altered expression of structural metabolism genes.…”
Section: Introductionmentioning
confidence: 99%